EDUCATION – WHAT FOR? FOR THE PHILOSOPHICAL FOUNDATIONS OF EDUCATION - Karikó, Sándor (PEOPLE: International Journal of Social Sciences, 2017)
I feel it necessary on both theoretical and methodological levels to think over the meaning, the possibilities and the challenges of philosophy of education, as well as its usability for our educational activities. Philosophy of education is part of the so-called applied philosophy, which examines the interconnection of the world, mankind and education. It tries to grab the characteristics and the deepest relationships among these three elements. Therefore, the educators, sociologists, philosophers and professors of education should continue working out convincing and steady answers. What we should take into consideration is that the matter of education itself is not identical to the process of education and socialisation. It would be advisable to find a solution to this issue in everyday pedagogical practices. Finally, I hope and I would like to believe that forming the goodness is the most noble and the most important mission of education.